Silylated MCM-41 Synthesized from RiceHusk - Ketcome, N; Grisdanurak, N (ASEAN Journal of Chemical Engineering, 2006)
Mesoporous material, MCM-41, synthesized from rice husk (RH-MCM-41) was modified by loading silylating agent (either Trimethylchlorosilane (TMCS), Dimethyl- dichlorosilane (DMCS) or Phenyl-trichlorosilane (PTCS)) in different concentration (1-9 %wt), and aging time, varied from I, 6, 9 and 24 hr. Properties of samples were characterized by XRD, Nz adsorption, FfIR, and TPD and adsorption of water, hexane, and toluene. Chemical modification resulted smaller pore size average and less surface area of RH-MCM-41, from 2.9 to 2.2 nm and from 900 to 500 mZ/g, respectively. PTCS could affect RH-MCM-41 surface structure more than other two. Adsorption behavior of modified RH-MCM-41 was also reflected to comparatively higher hydrophobicity.